Bu4NHSO4‐Catalyzed Direct N‐Allylation of Pyrazole and its Derivatives with Allylic Alcohols in Water: A Metal‐Free, Recyclable and Sustainable System. Issue 24 (27th September 2021) - Zhuang, Hongfeng; Lu, Nan; Ji, Na; Han, Feng; Miao, Chengxia
Abstract: Allylic amines are valuable and functional building blocks. Direct N ‐allylation of pyrazole and its derivatives as an atom economic strategy to provide allylic amines has been achieved only using commercial Bu4 NHSO4 as the metal‐free catalyst and water as the solvent without any additives. 11–93% isolated yields were obtained for the N ‐allylation of pyrazole and its derivatives with allylic alcohols. Bu4 NHSO4 could be reused for six times by simple extraction nearly without loss of catalytic activity and was also suitable for a gram‐scale production. The reaction of allylic ether and pyrazole did not occur to give the desired product indicated that allylic ether was not the active intermediate in the pathway. Density functional theory (DFT) calculations reveal that there are hydrogen bonding effects among substrates, solvent and catalyst, especially the one formed between allylic alcohol and H2 O. Control experiments in different protic solvents further demonstrate the intermolecular hydrogen bonding of allylic alcohol and water. Abstract :